The news from poems : essays on the 21st-century American poetry of engagement - Gray, Jeffrey, 1944-; Keniston, Ann, 1961- (Ann Arbor : University of Michigan Press, 2016)
"The News from Poems examines a subgenre of recent American poetry that closely engages with contemporary political and social issues. This "engaged" poetry features a range of aesthetics and focuses on public topics from climate change, to the aftermath of recent wars in Afghanistan and Iraq, to the increasing corporatization of U.S. culture. The News from Poems brings together newly commissioned essays by eminent poets and scholars of poetry and serves as a companion volume to an earlier anthology of engaged poetry compiled by the editors. Essays by Bob Perelman, Steven Gould Axelrod, Tony Hoagland, Eleanor Wilner, and others reveal how recent poetry has redefined our ideas of politics, authorship, identity, and poetics. The volume showcases the diversity of contemporary American poetry, discussing mainstream and experimental poets, including some whose work has sparked significant controversy. These and other poets of our time, the volume suggests, are engaged not only with public events and topics but also with new ways of imagining subjectivity, otherness, and poetry itself"--
Introduction : Contemporary poetry and the public sphere / Jeffrey Gray and Ann Keniston -- Part one : Redefining the political. Homeland insecurity and the poetry of engagement / Eleanor Wilner -- The poetry of engagement and the politics of reading / Vernon Shetley -- Twenty-first-century ecopoetry and the scalar challenges of the anthropocene / Lynn Keller -- Part two : Redefining authorship. The politics of docupoetry / Joseph Harrington -- "Hands off" : official language in contemporary poetry / Jeffrey Gray -- Delivering difficult news / Bob Perelman -- Part three : Redefining identity. Frank Bidart's poetics of engagement / Steven Gould Axelrod -- Beyond Katrina : ecopoetics, memory, and race / James McCorkle -- Claudia Rankine and the body politic / Elisabeth A. Frost -- Part four : Redefining poetics. Echo revisions : repetition, politics, and the problem of value in contemporary engaged poetry / Ann Keniston -- Ambivalence and despair / Kevin Prufer -- Getting the world into the poem : information, layering, and the composite poem / Tony Hoagland.
Includes bibliographical references and index.
Description based on print version record.
JSTOR
Keywords: Universidad Sergio Arboleda; American poetry -- 21st century -- History and criticism; Politics and literature -- United States -- History -- 21st century; Literature and society -- United States -- History -- 21st century; Poetics; Politique et littérature -- États-Unis -- Histoire -- 21e siècle.; Littérature et société -- États-Unis -- Histoire -- 21e siècle.; Poétique.; LITERARY CRITICISM / Poetry; American poetry; Literature and society; Poetics; Politics and literature; United States; Politische Lyrik; 2000-2099; Criticism, interpretation, etc; History